Highly Chemoselective, Transition-Metal-Free Transamidation of Unactivated Amides and Direct Amidation of Alkyl Esters by N-C/O-C Cleavage - Li, Guangchen; Ji, Chong-Lei; Hong, Xin; Szostak, Michal (Journal of the American Chemical Society, 2019)
The amide bond is one of the most fundamental functional groups in chemistry and biology and plays a central role in numerous processes harnessed to streamline the synthesis of key pharmaceutical and industrial molecules. Although the synthesis of amides is one of the most frequently performed reactions by academic and industrial scientists, the direct transamidation of tertiary amides is challenging due to unfavorable kinetic and thermodynamic contributions of the process. Herein, we report the first general, mild, and highly chemoselective method for transamidation of unactivated tertiary amides by a direct acyl N-C bond cleavage with non-nucleophilic amines. This operationally simple method is performed in the absence of transition metals and operates under unusually mild reaction conditions. In this context, we further describe the direct amidation of abundant alkyl esters to afford amide bonds with exquisite selectivity by acyl C-O bond cleavage. The utility of this process is showcased by a broad scope of the method, including various sensitive functional groups, late-stage modification, and the synthesis of drug molecules (>80 examples). Remarkable selectivity toward different functional groups and within different amide and ester electrophiles that is not feasible using existing methods was observed. Extensive experimental and computational studies were conducted to provide insight into the mechanism and the origins of high selectivity. We further present a series of guidelines to predict the reactivity of amides and esters in the synthesis of valuable amide bonds by this user-friendly process. In light of the importance of the amide bond in organic synthesis and major practical advantages of this method, the study opens up new opportunities in the synthesis of pivotal amide bonds in a broad range of chemical contexts.